An overview of the loquat's (Eriobotrya japonica) active components - Shahad Basheer Bahedh - Dina Yousif Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The variety known as loquat (Eriobotrya japonica (Thunb.) Lindl.) is subtropical in nature. The primary cultivators of loquat are China and Spain. It has a substantial nutritional composition, that is high in minerals, organic acids, vitamins, and carbohydrates. Moreover, a variety of bioactive substances, including flavonoids, triterpenoids, carotenoids, and phenolics, are abundant in loquat. These substances exhibit various biological properties, including cytotoxic, hypolipidemic, hypoglycemic, antioxidant, and antitumor properties. Numerous investigations carried out in vitro and in vivo have shown that loquat may have health benefits. To establish a link between the bioactive compounds and their biological activities, more research is necessary, thereby augmenting our understanding of the properties of this plant.